The Influence Of The Marketing Mix On Consumer Purchase Decisions At Ud Various Gypsum Gowa District - Ratri Beby Atul Mutiara; Dian AS Parawansa; Muhammad Ismail (Jurnal Mirai Management, 2023)
This study aims to determine the effect of the marketing mix on consumer purchasing decisions at Aneka Gypsum UD, Gowa Regency. The variables used in this research are product, price, promotion, and place as the independent variables while the purchase decision is the dependent variable. This research is a quantitative research. The data source in this study used primary data where data collection used the questionnaire method and the sample determination method used was the slovin formula so that a sample of 314 respondents was obtained. The results show that the T test (partial) on the product, price, and place variables has a positive and significant effect on purchasing decisions while promotion does not have a positive and significant effect on purchasing decisions. by F test (simultaneous) on product, price, promotion and place variables have a significant effect on purchasing decisions. Keywords: Product, Price, Promotion, Place, Purchase Decision